Efforts to Improve IPS Concept Understanding Through Discovery Learning Model Assisted by Visual Audio Learning Media in Basic School Students - Nofiyanto, Nofiyanto (Universitas Sebelas Maret, 2020)
The problem in this research is how the application of discovery learning model assisted by audio-visual media can improve understanding of social studies concepts in elementary school students? Purpose To determine the application of discovery learning model assisted by audio-visual media can improve understanding of social studies concepts in elementary school students. The object of this research is the fourth grade students of SD UMP. The data collection technique is carried out systematically with standard procedures, namely, learning outcome data is taken through tests at the end of each cycle and observation of student participation. The data were analyzed using quantitative and qualitative analysis of the formative test results. Then, the results of the calculations were consulted with the success criteria, to determine whether they were complete or not. Based on the results of the evaluation test from the first and second cycles, an increase in learning completeness was obtained. In the first cycle achieving learning outcomes with completeness 68%. In the second cycle the completeness of learning outcomes was 82%. Based on the findings and the results obtained in the study, it can be concluded that, through the discovery learning model assisted by audio-visual media, it can improve understanding of the social studies concept in elementary school students, but it still needs to be improved in cycle III.